The little merienda book - Gonzalez, Gene (Pasig City, 2004)
The cookbook features a range of accessible recipes, blending classic techniques with innovative twists to showcase the rich, diverse flavors of Filipino snack cuisine.
Keywords: Cookery, Philippine